2017
DOI: 10.5005/jp-journals-10057-0035
|View full text |Cite
|
Sign up to set email alerts
|

Biofilm Production in Clinical Isolates and Their Antimicrobial Susceptibility Pattern in the Intensive Care Unit of a Tertiary Care Hospital in Rajasthan

Abstract: Aims and objectives:This study was carried out to know about the production of biofilm by the microorganisms in various clinical isolates and to compare the antimicrobial sensitivity pattern of biofilm-and nonbiofilm-producing organisms. Materials and methods:One hundred and fifty samples collected from intensive care units for a period of 1 year were taken for the study. Samples included blood, urine, sputum, endotracheal tips, suction tips, pus/swabs, stents/valves, body fluids, etc. Samples were processed a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 55 publications
0
1
0
Order By: Relevance
“…In this study maximum Biofilm production were shown by Klebsiella pneumonaie (24.29%), Citrobacter species (23.07%), Escherichia coli (17.20%), Acinetobacter baumannii (22.22%) & Pseudomonas aeruginosa(12.96%) while study done by Malvika et al 28 showed maximum biofilm production in E.coli (78.5%) followed by Pseudomonas aeruginosa (82%), Acinetobacter species(90%).…”
Section: Discussionmentioning
confidence: 46%
“…In this study maximum Biofilm production were shown by Klebsiella pneumonaie (24.29%), Citrobacter species (23.07%), Escherichia coli (17.20%), Acinetobacter baumannii (22.22%) & Pseudomonas aeruginosa(12.96%) while study done by Malvika et al 28 showed maximum biofilm production in E.coli (78.5%) followed by Pseudomonas aeruginosa (82%), Acinetobacter species(90%).…”
Section: Discussionmentioning
confidence: 46%